Emergency situation analysis: On the example of underground mining radio communication system - Bazargur, Batzorig; Bataa, Otgonbayar; Budjav, Uuganbayar (Proceedings of the Mongolian Academy of Sciences, 2021)
Underground mine is the most dangerous environment for miners to work in, and the miners need to be evacuated immediately in case of an accident. This article aims to develop route options for safe emergency evacuation of miners from areas where there are no radio communication in underground mine to an area where radio communication is available in the underground mine on the example of an underground mine radio communication system. We have used the Dijkstra's algorithm in the study to determine the optimization of the short-term evacuation of miners in case of an accident in an underground mine. We have also developed the optimization of evacuation route to a place where there is radio communication failure owing to an accident to a place where normal radio communication is available. Using MATLAB it was possible to analyze the shortest route for evacuation from an area without communication to an area with normal communication, and for this purpose it gave us the possibility to analyze using any number of exits. The novelty of the study was using the shortest route option on the example of radio communication failure in an underground mine.